Bhabha for architects - Hernandez, Felipe (New York, N.Y. : Routledge, 2010)
Introduction : Bhabha's theoretical context ; Postcolonial theory ; Bhabha and architecture ; The plan of this book
Dizin (sayfa 137-143) içerir.
Keywords: Bhabha, Homi K., -- 1949-; Architecture -- Philosophy; Mimarlık -- Felsefe